Anaesthetic Considerations in Emergency Lower Segment Caesarean Section in Preeclamptic Parturient with Neurofibromatosis: A Case Report - Charmi Hitenbhai Shah; Upasna Vineet Bhatia; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Neurofibromatosis type I (NF1) is an autosomal dominant genetic disorder characterised by multiple cutaneous manifestations and potential systemic involvement that can complicate anaesthetic management, especially in obstetric patients. This case report describes the anaesthetic management of a 27-year-old primigravida with NF1 and preeclampsia who presented to obstetric department for emergency cesarean delivery due to foetal distress. The patient displayed classic NF1 features including café-au-lait spots and multiple cutaneous neurofibromas. Airway assessment revealed Mallampati Grade III classification without palpable oropharyngeal masses. Given the emergency situation and potential airway challenges, general anaesthesia was selected using rapid sequence induction with propofol and succinylcholine. Anaesthesia was maintained with oxygen, nitrous oxide, sevoflurane, and atracurium, with fentanyl administered after delivery. The patient maintained stable haemodynamics throughout the procedure despite preeclampsia with baseline blood pressure of 140/100 mmHg. Despite the potential for difficult airway management and cardiovascular complications in patients with NF1, the perioperative period was uneventful with successful mother and baby outcomes. This case emphasises the importance of thorough preoperative assessment, anticipation of potential complications, and a tailored anaesthetic approach in managing parturients with NF1, particularly in emergency scenarios complicated by preeclampsia.